The Anatolian Journal of Cardiology 2022
DOI: 10.5152/anatoljcardiol.2021.24850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Alcohol Consumption Levels on the Left Atrial Size: a Cross-sectional Study in Rural China

Abstract: Objective: Previous studies have investigated the relationship between alcohol and ventricular structure; however, few studies have evaluated the relation between alcohol consumption and the atrium size. In this study, we aimed to test the association between alcohol consumption and left atrium (LA) size in the general population. Methods: A population-based sample of 10,211 subjects aged ≥35 years and free from hypertension at baseline were followed from January 2012 to August 2013. Left atrial enlargement (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In 5220 participants of the Framingham Heart Study, alcohol was identified as a predictor of LA enlargement and incident AF in a dose-dependent manner [ 150 ]. Similarly, in a cross-sectional study in rural China with 10,211 participants that were aged 35 and above, moderate and heavy alcohol consumption was significantly associated with the risk of LA enlargement [ 151 ]. Among 601 participants with stable coronary heart disease with echocardiographic measurements at baseline and 5 years later, alcohol use at baseline was associated with an increase in left atrial volume [ 152 ].…”
Section: Atrial Myocardium and Alcoholmentioning
confidence: 99%
“…In 5220 participants of the Framingham Heart Study, alcohol was identified as a predictor of LA enlargement and incident AF in a dose-dependent manner [ 150 ]. Similarly, in a cross-sectional study in rural China with 10,211 participants that were aged 35 and above, moderate and heavy alcohol consumption was significantly associated with the risk of LA enlargement [ 151 ]. Among 601 participants with stable coronary heart disease with echocardiographic measurements at baseline and 5 years later, alcohol use at baseline was associated with an increase in left atrial volume [ 152 ].…”
Section: Atrial Myocardium and Alcoholmentioning
confidence: 99%
“…Based on sporadic case experiences, experiments on animal models have been conducted, and the adverse effects of these beverages on various organ systems have been revealed when used alone or in combination with alcohol. 4 - 8 …”
Section: Introductionmentioning
confidence: 99%